Wittgenstein and the Politics of Vision - Chmielewski, Adam
: In this paper some insights from the contemporary theory of vision are employed to delineate a conception of political aesthetics. By tracing the evolution in the theory of vision from Wittgenstein’s seeing-as, through Ernst Gombrich’s seeing-into, Richard Wollheim’s seeing-in, to Emmanuel Alloa’s seeing-with, I contend that while the sense of sight is a natural human endowment, the ability to see, just as other abilities, needs to be learned through a collective process which I call seeing-with-others. I argue that Wittgenstein’s repudiation of his own early view of perception may help to undermine the belief that seeing is a disinterested, impartial, and unbiased cognitive activity. Through reference to Wittgenstein’s idea of the captivating effect of a picture, I claim that mastering the art of seeing requires mastering the rules of sensory orders, or perceptual regimes, which are sustained by a collective perceptual hysteresis, and which enable one to see the reality in a specifically ordered way. I argue that human individual perceptive faculties are inescapably exposed to various influences that contribute to their contents and, more importantly, play a crucial role in the emergence and development of perceptive abilities in the first place. Since all cognitive subjects unavoidably participate to a varying degree in the enactive constitution of perceptual regimes, such interactive processes may be interpreted as democratic, though not in the consensual but in an agonistic sense.
Keywords: aspect-perception; regime of perception; perceptual hysteresis; political aesthetics